Effects of Sildenafil in Nω-Nitro-l-Arginine Methyl Ester–Induced Intrauterine Growth Restriction in a Rat Model - Abi Nader, Khalil (2012)
Objective To assess the effect of sildenafil citrate in a rat model of Nω-nitro-l-arginine methyl ester (L-NAME)-induced intrauterine growth restriction (IUGR). Study Design An in vivo experimental study was conducted where 40 pregnant Sprague-Dawley rats were randomly assigned to receive either: (1) control, (2) L-NAME 50 mg/kg/d by gavage (days 14 to 19), (3) L-NAME and sildenafil 15 mg/kg/d by gavage, or (4) sildenafil (days 14 to 21). On day 21, a hysterotomy was performed and all fetuses (live and dead) were counted, examined, and weighed. The primary outcome measure was the difference in pup birth weight. Results The median number of live pups per dam was 11.5 (range: 1 to 15), 13.5 (2 to 17), 13.5 (7 to 16), and 11.5 (4 to 17) in controls, L-NAME, sildenafil, and combined drug groups, respectively (p = 0.02). Rats treated with L-NAME had a significantly higher number of stillbirths compared with control (p = 0.013) and sildenafil (p = 0.008) groups. L-NAME reduced pup birth weight compared with controls (4.53 ± 1.49 versus 5.65 ± 1.63 g, p < 0.001); this effect was more pronounced in the L-NAME and sildenafil groups (3.37 ± 1.25 g, p < 0.001). Conclusion Our data indicate that sildenafil citrate does not ameliorate L-NAME-induced IUGR, and in the doses utilized in this study might even have a synergistic negative effect on pup birth weight.